The Impact of Local Economic Growth Target Setting on the Quality of Public Occupational Health: Evidence From Provincial and City Government Work Reports in China - Wang, Fan-Fan; Deng, Wen-Jing; Cheng, Hao; Gao, Qing; Deng, Zi-Wei; Deng, Han-Cong (Frontiers in Public Health, 2021)
This article uses data from the government work reports of 31 provinces (autonomous regions and municipalities) in China and 21 cities in Guangdong Province of China to perform a fixed effect regression. It was found that economic growth target constraints and economic growth target gaps between countries and provinces, or between provinces and cities have a significant impact on the quality of public occupational health. The non-linear relationship between economic growth target setting and the quality of public occupational health was then discussed in detail, and the reliability of basic conclusions drawn was ensured by robustness and endogeneity tests. The results show that the effect of economic growth target constraints and gaps on the quality of public occupational health shows a “U-shaped” trend at both the provincial and city levels, which initially promotes and, eventually, inhibits. This relationship is closely related to the current economic system reforms, administrative reforms, and social transformation in China. Therefore, in emphasising high-quality economic development, the government should fully consider the actual state of the development of jurisdictions in setting economic goals to improve the quality of public occupational health in an orderly manner.